Nutritional Status of Diabetic Patients Attending to a District Level Diabetic Center - Begum, FAM Anjuman-Ara; Azad, Abdul Kalam; Alim, M Abdul; Ekram, ARM Saifuddin (TAJ: Journal of Teachers Association, 2009)
A total of 117 diabetic patients aged 20-65 years suffering from diabetes for at least one year were enrolled in this cross-sectional study. The study was conducted in Nawabganj Diabetic Center, a branch of Bangladesh Diabetic Association during the period from March 2001 to June 2001. The aim of the study is to assess the nutritional status of diabetic patients, which may contribute useful information for more comprehensive and intensive approach to diabetic patients care. Majority (64%) of the respondents were normal (BMI 18.5-24.99) in nutritional status followed by overweight (31%, BMI > 25) and underweight (4.3%, BMI < 18.5). Middle age group appeared to suffer more from diabetes with no sex difference irrespective of age (males: 50.4%, females: 49.6%). Diabetic care seeking behaviour by rural people and females (housewives) appeared encouraging emphasizing the need of decentralization of diabetic care center to periphery. More retired persons (50%) and housewives (32%) showed obesity (40%) and no underweight with high family income might be explained as an association of more calorie intake and less physical activities. Among the diabetic patients, retired persons and housewives appeared particularly vulnerable to become obese and on the other hand younger patients, poor education, lower income group and patients consuming low calorie were prone to develop under nutrition. So health education should be aimed to enhance awareness of particularly rural and illiterate people for regular visit to nearby diabetic center and to strictly adhere to dieticians' advice. doi: 10.3329/taj.v17i2.3451 TAJ 2004; 17(2): 89-92